2021
DOI: 10.1016/j.jse.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Opioid consumption following orthopedic shoulder surgery: a retrospective analysis

Abstract: Background: Prescription opioid misuse has become an epidemic in the United States and is a leading cause of death in Americans. Postoperative opioid prescriptions are a significant contributor to the opioid epidemic, with orthopedic surgeons being the third highest prescribers of opioid prescriptions among physicians across all specialties. Our aim was to retrospectively evaluate overall opioid consumption patterns following surgical treatment for shoulder pathology and recommend evidence-based guidelines for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
2
1
0
Order By: Relevance
“…27,28 To the best of our knowledge, this is the first study to systematically build and vali-date a model that predicts the quantity of outpatient opioids used after discharge by patients who underwent cesarean birth (PubMed search query: ["Forecasting"{Mesh} OR forecasting{tiab} OR predictive Multiple studies have examined associations between patient or surgical characteristics and postdischarge opioid use. [29][30][31][32][33] Our study is consistent with previous observed associations. Studies from the surgical literature consistently find associations between inpatient and outpatient opioid use, but findings related to tobacco use and depression or anxiety are mixed and largely depend on whether these data were collected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…27,28 To the best of our knowledge, this is the first study to systematically build and vali-date a model that predicts the quantity of outpatient opioids used after discharge by patients who underwent cesarean birth (PubMed search query: ["Forecasting"{Mesh} OR forecasting{tiab} OR predictive Multiple studies have examined associations between patient or surgical characteristics and postdischarge opioid use. [29][30][31][32][33] Our study is consistent with previous observed associations. Studies from the surgical literature consistently find associations between inpatient and outpatient opioid use, but findings related to tobacco use and depression or anxiety are mixed and largely depend on whether these data were collected.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have examined associations between patient or surgical characteristics and postdischarge opioid use. 29–33 Our study is consistent with previous observed associations. Studies from the surgical literature consistently find associations between inpatient and outpatient opioid use, but findings related to tobacco use and depression or anxiety are mixed and largely depend on whether these data were collected.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, acetaminophen (i.e., Tylenol) and non-steroidal anti-inflammatory drugs (NSAIDs) have shown remarkable effectiveness in multimodal analgesia studies. 5,7,12,19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] We recommend against using opioidacetaminophen combination medications to avoid confusion and minimize possible accidental acetaminophen overdose. Tramadol, a synthetic analog of codeine, can be an effective alternative to traditional opioids for mild-moderate postoperative pain.…”
Section: Strategiesmentioning
confidence: 99%